(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Human resources planning that is hard-wired with good will support the quality of prospective employees as well as the number of types of labour required at any given time, so being able to help the recruitment of employees. the process of recruitment of prospective employees who have the ability to work in a company. PT PLN (Persero) conducts recruitment with several stages of recruitment, i.e. registration of participants, calling on the participants to the process of administration by bringing files that had been noted at the time of registration, selection of administration, general aptitude test, academic and English, the psychological test, interview and health tests. the environment PT PLN (Persero) is a public company engaged in the service so it has a great responsibility to be able to provide the best service to the community. The company is one of the strategic initiatives prepared for transforming human resources (human capital). to form a quality workforce then need to determine qualifications regarding labor is needed and put it in the right position, so that the company’s goals will be achieved. to achieve the objectives of the company then needed a good workforce planning for each Division or Department within the company. The implementation of the recruitment policy of the State electricity company PT. (Persero) Region Suluttenggo. Views of 6 Implementation according to the theory of van meter and van horn that is standard policy and objectives, resources, implementing agencies/implementor, implementer of the attitudes, communication, social conditions, economic, political. This research is a descriptive qualitative approach method through indepth interviews to 8 people additional observations, the informant in the form of a list of guidelines for interviews and writing stationery. The results showed in general recruitment policy Implementation Employees of the State electricity company PT has not gone well. Keyword: Employee Recruitment Policy Implementation